2014
DOI: 10.1016/j.cub.2014.01.071
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Transcriptional and Metabolic Programs Related to Mammalian Cell Size

Abstract: SummaryBackgroundRegulation of cell size requires coordination of growth and proliferation. Conditional loss of cyclin-dependent kinase 1 in mice permits hepatocyte growth without cell division, allowing us to study cell size in vivo using transcriptomics and metabolomics.ResultsLarger cells displayed increased expression of cytoskeletal genes but unexpectedly repressed expression of many genes involved in mitochondrial functions. This effect appears to be cell autonomous because cultured Drosophila cells indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

28
143
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 118 publications
(171 citation statements)
references
References 36 publications
28
143
0
Order By: Relevance
“…Lipid biosynthesis pathways and their transcriptional controllers, including the sterol regulatory element binding proteins (SREBPs), are downregulated at the mRNA level in vivo when proliferation 25 is prevented and cells increase in size [13]. Conceptually, these observations are consistent with the reasoning that larger cells have a reduced SV ratio and, consequently reduced need for plasma membrane lipids.…”
Section: Mitochondria In Cell Size Controlsupporting
confidence: 72%
See 4 more Smart Citations
“…Lipid biosynthesis pathways and their transcriptional controllers, including the sterol regulatory element binding proteins (SREBPs), are downregulated at the mRNA level in vivo when proliferation 25 is prevented and cells increase in size [13]. Conceptually, these observations are consistent with the reasoning that larger cells have a reduced SV ratio and, consequently reduced need for plasma membrane lipids.…”
Section: Mitochondria In Cell Size Controlsupporting
confidence: 72%
“…We found that the rate at which mitochondrial activity was reduced with 25 increasing cell size also reacted to temperature as predicted by these mathematical models of allometric scaling [34]. Consistently, we have previously observed that mitochondria associated genes display a relative reduction in mRNA levels in response to increases in hepatocyte size in vivo [13]. This downregulation of mitochondria-related gene expression likely reflects the reduced demand for mitochondrial function in larger cells.…”
Section: Mitochondria In Cell Size Controlsupporting
confidence: 66%
See 3 more Smart Citations